Patterns and possible causes of skewed sex ratios in American lobster (Homarus americanus) populations. Issue 3 (3rd July 2019) - Jury, SH; Pugh, TL; Henninger, H; Carloni, JT; Watson, WH
ABSTRACT: Multiple studies have identified sex ratios in adult American lobster ( Homarus americanus ) populations that are skewed toward males in some locations and females in others. The mechanisms leading to these differences, and the subsequent ecological implications, have been reported to be a result of sexual differences in fishing mortality due to sex specific regulations, catchability, or behaviour. In particular, seasonal migrations in response to fluctuating environmental conditions, including temperature and salinity, can lead to skewed sex ratios of lobsters in estuaries, nearshore coastal and offshore habitats. In this review we focus on four relatively well-studied American lobster populations that are consistently male or female dominated: 1) The Great Bay Estuary, New Hampshire; 2) The Isles of Shoals, off the coast of New Hampshire and southern Maine; 3) Buzzard's Bay, Massachusetts and; 4) Georges Bank. We review the available data and discuss the various hypotheses that have been put forth to explain the underlying causes of the skewed sex ratios in each area. We then outline possible changes in reproduction that may be expected if sex-specific changes in local distributions of lobsters shift further due to climate change.